Evaluation of Nanomechanical Properties, Surface Roughness, and Color Stability of Esthetic Nickel-Titanium Orthodontic Archwires - Alsanea, Jamal A (J Int Soc Prev Community Dent, 2019)
OBJECTIVES: The objective of the study is to evaluate the surface roughness, nanomechancial properties the color stability of three brands of coated (rhodium, epoxy, and Teflon) nickel-titanium (NiTi) esthetic archwires. MATERIALS AND METHODS: Three brands of coated (rhodium, epoxy, and Teflon) esthetic NiTi archwires and three brands of uncoated (NiTi) archwires from the same manufactures were evaluated for the surface roughness, nanomechanical properties, and color stability. The specimens with 20 mm length (n = 5) were cut from the straight buccal segments of the coated and uncoated archwires. The specimens with 20 mm length (n = 10) were subjected to color measurement after immersion in a coffee staining solution. The color measurement was evaluated after 7, 14, 21, and 28 days after immersion in staining solution using color eye 7000 spectrophotometer. The experimental data were analyzed using descriptive statistics, analyses of variance, and Tukey's post hoc test. RESULTS: Epoxy (1.517 ± 0.071) and rhodium (0.297 ± 0.015) coated archwires showed the highest and lower value of surface roughness. All the intergroup comparisons showed a significant difference (P < 0.05) in surface roughness except between rhodium and control group (P = 0.998). There were significant differences between control and the experimental groups for both nanohardness and elastic modulus was observed. All the three NiTi-coated esthetic archwires demonstrated trace” (extremely slight change) color changes as measured by the National Bureau of Standards units after 4 weeks of immersion. CONCLUSION: Surface roughness of rhodium-coated archwires was almost similar to that of uncoated wires. Whereas Teflon and epoxy coated archwires showed a significant difference in surface roughness compared to uncoated archwires. Uncoated archwires showed higher nanohardness values compared to the coated archwires. Teflon-coated archwires demonstrated significantly slight color change after 4 weeks of immersion in staining solution.